Mrs. Morris and the mermaid - Wilton, Traci (Wilton, Traci. Salem B&B mystery, 2024)
"B&B owner Charlene Morris expects Salem's first annual mermaid parade will make quite a splash, until a high-profile murder threatens to sink the whole event...Charlene and her handsome spectral friend, Dr. Jack Strathmore, are thrilled that their Salem, Massachusetts, B&B is overflowing with mermaids in advance of the town's newest attraction--a mermaid parade! Retired Hollywood actress Trinity Powers has even agreed to appear on the lead float to commemorate her breakout role as the eponymous mermaid in the blockbuster cult classic, Sirena. The parade also features Trinity's rival, an up-and-coming inǧnue, who stars in the film's recent (and somewhat controversial) reboot. Though their rabid fan clubs seem ready to tear each other--and the festivities--apart, the vying actresses are keeping it cool, for now...But when Charlene discovers a mermaid murdered, she realizes a killer is out to steal the show. With the help of Jack and Detective Sam Holden, Charlene plunges into the case, determined to stop a killer from striking again..."--